Whose Family Name upon Birth and Marriage? Macedonian and European PIL Perspectives - Deskoski, Toni; Dokovski, Vangel (Faculty of Law, University of Niš, 2016)
This article is an examination of the issues of family name in private international law with main focus to the situations of birth and marriage. It provides a comparative overview of the current situation in the EU Private International Law and in the Macedonian Private International Law This analysis considers also the extent to which the law and culture in the European Context are interconnected. The main hypothesis in this article is that the Laws governing names have function as a form of social control. Hence, all states are using their legislative power to determine content, right and protection of the family name.